A comparative review on freshwater fish fauna between West Bengal and Odisha, two middle-east Indian states - Angsuman Chanda; Arun Jana (Journal of Fisheries, 2021)
The objective of the present study is the comparative revision of inland freshwater fish faunal diversity between West Bengal and Odisha, two states of middle-east India. Work is mainly based on the available published literature on the freshwater fish faunal diversity, checklist for fish, monograph of the area under study. Result reveals the existence of 345 species of fish belonging to 50 families under 14 orders. Analysis of data shows a slight similarity of freshwater fish faunal diversity between two states is quite expected because both the states differ in their physiography and ecology. The present report may serve as a helpful document for freshwater aquaculturists as well as fishery researchers for their future planning of research work on the subject of the study area.